2006
DOI: 10.1111/j.1365-2672.2005.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference in adhesion of bacteria and yeasts isolated from explanted voice prostheses to silicone rubber by rhamnolipid biosurfactants

Abstract: Aims: The effects and extent of adhesion of four different bacterial and two yeast strains isolated from explanted voice prostheses to silicone rubber with and without an adsorbed rhamnolipid biosurfactant layer obtained from Pseudomonas aeruginosa DS10-129 was studied. Methods and Results: The ability of rhamnolipid biosurfactant to inhibit adhesion of micro-organisms to silicone rubber was investigated in a parallel-plate flow chamber. The anti-adhesive activity of the biosurfactant at different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 40 publications
1
85
0
9
Order By: Relevance
“…Several reports have suggested that, in addition to their direct action against pathogens, biosurfactants are able to interfere with biofilm formation, modulating microbial interaction with interfaces (Federle & Bassler 2003;Merk et al, 2005;Neu, 1996;Rasmussen & Givskov, 2006;Rodrigues et al, 2006bRodrigues et al, , 2006cRodrigues et al, 2007). Surfactin for example has shown to be an important part of a list of biofilm controlling agents.…”
Section: Biofilms On Medical Devicesmentioning
confidence: 99%
“…Several reports have suggested that, in addition to their direct action against pathogens, biosurfactants are able to interfere with biofilm formation, modulating microbial interaction with interfaces (Federle & Bassler 2003;Merk et al, 2005;Neu, 1996;Rasmussen & Givskov, 2006;Rodrigues et al, 2006bRodrigues et al, , 2006cRodrigues et al, 2007). Surfactin for example has shown to be an important part of a list of biofilm controlling agents.…”
Section: Biofilms On Medical Devicesmentioning
confidence: 99%
“…Superfícies de borracha de silicone condicionadas com ramnolipídios de P. aeruginosa, obtiveram inibições na adesão de 60,9 %, 53,1 %, 58,2 % e 33,8 % contra as bactérias R. dentocariosa, S. epidermidis, S. salivarius e S. aureus, respectivamente, com solução de ramnolipídio não diluída (4 g/L). 97 99 Estes dados reforçaram a ideia de que alguns biossurfactantes são efetivos na inibição da adesão de acordo com as características das superfícies. Foi comprovado que a B. kururiensis possui o sistema HSL de quorum sensing, chamado de BraI/R, que produz e responde ao 3-oxo-C 12 -HSL e é extremamente similar ao LasI/R de P. aeruginosa (nesta é interconectado com outros sistemas regulatórios e é o regulador global envolvido na regulação de muitos genes que possuem importância na virulência e colonização).…”
Section: Propriedades Antibiofilmes Dos Biossurfactantesunclassified
“…Dessa forma, a partir dos resultados encontrados, pode-se afirmar que o método do AVC para as estirpes de Salmonella spp., utilizadas neste experimento não pode ser considerado como teste presuntivo válido para a avaliação da produção de biofilme, conforme vem sendo utilizado para estirpes de S. aureus cuja eficiência já é comprovada (STEPANOVIC et al, 2004;RODRIGUES et al, 2006) …”
Section: Avaliação Da Produção De Cápsulaunclassified
“…strains isolated from aviary and slaughter line of chicken in a fridge of Rio Grande do Sul state to produce biofilms and be resistant to carbapenems antibiotics. In the evaluation of biofilm production, it was used the polyethylene microplates and capsule production technique according to Stepanovic et al (2004) and Rodrigues et al (2006), respectively. The virulence factors of salmonella were researched, represented by the genes IpfA, agfA, sefA, invA, hilA, avrA, sopE, sivH,e spvC, using the Polymerase Chain Reaction (PCR) method described by Borges et al (2013).…”
Section: Evaluation Of Biofilm Production Capacity and Detection Of Ementioning
confidence: 99%
See 1 more Smart Citation